2004
DOI: 10.2746/0425164044848226
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic evaluation of the back in the sport horse with back pain

Abstract: Summary Reasons for performing study: Earlier studies have developed a clinical tool to evaluate objectively the function of the equine back. The ability to differentiate horses with back pain from asymptomatic, fully functioning horses using kinematic measures from this tool has not been evaluated. Objectives: To compare the kinematics of the back at walk and trot in riding horses with back dysfunction to the same parameters in asymptomatic sport horses. Methods: The kinematics of the back in 12 horses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 19 publications
(24 reference statements)
7
72
0
1
Order By: Relevance
“…A later study found maximal amplitudes of pelvic long-axis rotation in the tree-shrew of approximately 5deg (Schilling and Fischer, 1999). Wennerstrand et al observed mean long-axis rotation of 6deg in the pelvis of sport horses (Wennerstrand et al, 2004). In the present study, a much larger amplitude of 27deg was measured for the long-axis rotation of the sloth pelvis.…”
Section: -D Thoraco-lumbar Spine Movements and Pelvic Displacementssupporting
confidence: 53%
See 1 more Smart Citation
“…A later study found maximal amplitudes of pelvic long-axis rotation in the tree-shrew of approximately 5deg (Schilling and Fischer, 1999). Wennerstrand et al observed mean long-axis rotation of 6deg in the pelvis of sport horses (Wennerstrand et al, 2004). In the present study, a much larger amplitude of 27deg was measured for the long-axis rotation of the sloth pelvis.…”
Section: -D Thoraco-lumbar Spine Movements and Pelvic Displacementssupporting
confidence: 53%
“…Although published quantifications of 3-D pelvic displacements during symmetric mammalian quadrupedalism are themselves scant (Jenkins and Camazine, 1977;Schilling and Fischer, 1999;Wennerstrand et al, 2004;Schmidt, 2005), the minute intervertebral movements associated with these displacements are even less well investigated. Efforts have been made to deduce intervertebral mobility from the morphology of the vertebrae (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Equine spinal motion has been assessed in great detail in vitro (Jeffcott and Dalin, 1980; 50 Townsend et al, 1983) muscle pain (Wennerstrand et al, 2004). However, the constriction of camera calibration makes 58 it difficult and the high cost of multiple specialist cameras required to cover large areas (e.g.…”
Section: Introduction 49mentioning
confidence: 99%
“…The horse's natural sport kinetic is affected with the presence of back pain (De Cocq, 2009), and have a limited range of motion of the thoracic spine for dorsoventral flexion and extension compared with asymptomatic horses (Wennerstrand et al, 2004). The lack of significant differences of the evaluated radiological signs found in the segments considered for analysis is disputable.…”
Section: Discussionmentioning
confidence: 93%